1971
DOI: 10.1017/s0022172400021823
|View full text |Cite
|
Sign up to set email alerts
|

An M-associated protein antigen (MAP) of group A streptococci

Abstract: SUiMARYA streptococcal antigen that is closely associated with the M-antigen, but is not type specific can be detected by means of a complement-fixation test in extracts of M-positive, but not of M-negative, variants of group A streptococci. Purification of acid extracts results in a concomitant increase in the purity both of the typespecific M-antigen and of the M-associated protein (MAP). Antibody to MAP is present in the sera of patients who have had streptococcal infection. The highest titres are found in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
74
0

Year Published

1974
1974
2012
2012

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 20 publications
1
74
0
Order By: Relevance
“…However, S. pyogenes strains are almost invariably bacitracin sensitive and possess T and M antigens (or M-associated protein; Widdowson, Maxted & Pinney, 1971); S. milleri, on the other hand, is resistant to bacitracin (Colman & Williams, 1972) and does not form surface-protein antigens characteristic of S. pyogenes.…”
Section: Discussionmentioning
confidence: 99%
“…However, S. pyogenes strains are almost invariably bacitracin sensitive and possess T and M antigens (or M-associated protein; Widdowson, Maxted & Pinney, 1971); S. milleri, on the other hand, is resistant to bacitracin (Colman & Williams, 1972) and does not form surface-protein antigens characteristic of S. pyogenes.…”
Section: Discussionmentioning
confidence: 99%
“…In our first report on the presence of this antibody in human sera (Widdowson et al 1971) we stated that titres were higher in rheumatic fever (range 60-320) than in nephritis (range 0-80) or in sporadic uncomplicated streptococcal infection of the throat (range 0-80). We had not at that stage examined a large number of sera from cases of uncomplicated sore throat in a single outbreak.…”
Section: Discussionmentioning
confidence: 90%
“…Anti-MAP titres were determined by a complement fixation test (CFT) with the purified M-protein of a type 30 strain (Widdowson, Maxted & Pinney, 1971). The use of a type 30 M-protein virtually rules out the possibility of fixation of complement by a patient's serum due to the presence of type-specific antibodies, since type-30 infections are extremely rare in Britain.…”
Section: Streptococcal Typingmentioning
confidence: 99%
“…Recent evidence has unearthed the fact that many human sera contain antibodies to a moiety(ies) of M-protein which is closely associated with, but distinct from, the type-specific determinant (13)(14)(15)(16)288 (14,16,288) and complement fixation (288). Titration of serum levels by the latter method have revealed that the highest titers are present in patients with ARF (13 (162).…”
Section: Immunological Evidencementioning
confidence: 99%